TALIBAN SEBAGAI FAKSI DI AFGHANISTAN DALAM PERSPEKTIF HUKUM INTERNASIONAL - Asih Puspaning Winahyu; Budi Parmono; Pinastika Prajna Paramita (Fakultas Hukum Universitas Islam Malang, 2022)
ABSTRACT The development of the subject of international law has led to the birth of rebel groups who demand their rights to a sovereign government in a region. The Taliban is an insurgent group founded by Mullah Omar in 1994 to fight political instability, corruption, and crimes that occurred in Afghanistan after the withdrawal of the Soviet Union from Afghanistan. Since the Taliban was founded until now there have been many deprivations of human rights carried out by the Taliban against the Afghan population. For example, girls who are 10 years old are prohibited from going to school, the ban on radio, television, and music broadcasting in Afghanistan. At the end of August 2021, the Taliban succeeded in overthrowing and taking over the Afghan government. This is what makes the international community confused regarding the statement of attitude towards the presence of the Taliban group. In this study, two basic questions become the object of research, namely: How is the position of the Taliban in the subject of international law and how is the recognition obtained by the Taliban after successfully controlling and leading Afghanistan according to international law. This research is normative juridical research using an international instrument approach, a conceptual approach, and a case approach. The results of this study are: the Taliban can be categorized as insurgent based on the characteristics and elements contained in the group, and the form of recognition obtained by the Taliban is in the form of acknowledging the new government, but the takeover of the government was carried out unconstitutionally (forced seizure). so the international community has not recognized it.Keywords: Taliban, Afghanistan, International LawÂ ABSTRAKPerkembangan subjek hukum internasional menyebabkan lahirnya kelompok pemberontak yang menuntut hak-haknya kepada pemerintahan yang berdaulat dalam suatu wilayah. Taliban merupakan kelompok pemberontak yang didirikan oleh Mullah Omar pada tahun 1994 dengan tujuan untuk ketidakstabilan politik, korupsi, serta kejahatan-kejahatan yang terjadi di Afghanistan pasca penarikan Uni Soviet dari Afghanistan. Sejak Taliban didirikan hingga saat ini banyak terjadi perampasan hak asasi manusia yang dilakukan oleh Taliban terhadap penduduk Afghanistan. Misalnya anak perempuan yang sudah berusia 10 tahun dilarang untuk tayangan, musik larangan radio, televisi serta di Afganistan. pada akhir Agustus 2021 lalu, Taliban berhasil menggulingkan dan mengambil alih pemerintahan Afghanistan. Hal tersebutlah yang membuat masyarakat internasional kebingungan terkait dengan pernyataan sikap akan kehadiran kelompok Taliban. Dalam penelitian ini terdapat dua pertanyaan mendasar yang menjadi objek penelitian, yaitu: Bagaimana kedudukan Taliban dalam subjek hukum internasional dan Bagaimana pengakuan (recognition) yang didapat oleh Taliban setelah berhasil menguasai dan memimpin Afghanistan menurut hukum internasional. Penelitian ini merupakan penelitian yuridis normatif dengan menggunakan pendekatan berupa instrumen internasional, pendekatan konseptual dan pendekatan kasus. Hasil dari penelitian ini yaitu: Taliban dapat dikategorikan sebagai pemberontak berdasarkan karakteristik serta unsur-unsur yang terdapat di dalam kelompok tersebut, dan bentuk pengakuan yang didapatkan oleh Taliban berupa pengakuan terhadap pemerintahan baru,Kata Kunci: Taliban, Afghanistan, Hukum InternasionalÂ